Atlas of ophthalmic surgery. Vol. III, Strabismus and glaucoma - Buckley, Edward G; Freedman, Sharon; Shields, M. Bruce; Waldrop, Thomas G (Mosby, 1995)
As part of a four-volume set, this atlas covers step-by-step depiction of anatomy, surgical procedures, preparations and incision for the ophthalmologist in cases of glaucoma and strabismus.
Keywords: glaukom; Glaucoma; Strabismus; oftalmologie; strabismus; chirurgie; General Surgery